5PSQ-055 Does palbociclib mean neutropaenia?. (March 2019) - Perez Contel, A; Soriano-Gutierrez, L; de Pedro Ambrosio, VJ; Miralles-Albors, P; Puig Comas, G; Fernandez-Molina, S; Gomez-Valent, M
Abstract : Background: Palbociclib is a cyclin-dependent kinases 4/6 inhibitor, indicated in metastatic or locally advanced breast cancer, hormone receptor-positive and HER2-negative. The treatment is performed until unacceptable toxicity or progression of the disease. In clinical trials PALOMA-2 and PALOMA-3, the haematological toxicity was very frequent. These adverse reactions may promote the permanent interruption of the treatment or the delay and/or reduction of the dose, and that could determinate the effectiveness of the treatment. Purpose: To describe the safety profile of palbociclib in clinical practice. Material and methods: The study included patients treated by at least two cycles with palbociclib, from November 2017 to July 2018, in a university hospital that covers almost 4 00 000 inhabitants. Data was extracted from the clinical history and the following variables were recorded in Microsoft Excel: age; absolute neutrophil count, haemoglobin and platelets at the start of treatment, at the fifteenth dayof treatment (first nadir) and before each cycle; other toxicities; degree of toxicities; dose reduction; and date and reason (toxicity/progression) of finishing the treatment. Results: Twenty patients were included, all females, with a median age of 61 years. Haematological toxicities observed were neutropaenia in all the patients, 35% anaemia, 25% thrombocytopaenia and 5% lymphopaenia, of any degree. Grade 3 neutropaenia was detected in 65% of patients and none of grade 4. Ninety per cent of patients presented neutropaenia of any degree at first nadir (39% grade 3). Grade 3–4 anaemia or thrombocytopaenia were not detected, but one patient suffered grade 3 lymphopaenia. Other toxicities: asthaenia (35%), rash (15%), stomatitis (10%), ocular alterations (10%) and anorexia, nasal dryness, diarrhoea or alopecia in 5% of patients. The dose was modified due to toxicity in 55% of patients: 20% of them required a second dose reduction. Any patient finished treatment due to toxicity. Conclusion: The frequency of neutropaenia in our sample was higher than reported in the prescribing information but similar in terms of anaemia and thrombocytopaenia frequency. More than half of the patients required dosage reduction, a greater proportion than observed in the randomised clinical trials. The main reason for dose reduction was neutropaenia so palbociclib and neutropaenia were closely related. References and/or acknowledgements: Oncology and pharmacy departments. No conflict of interest.